Family caregiving in the new normal - Gaugler, Joseph E.; Kane, Robert L., 1940-2017 (London [England] : Academic Press, an imprint of Elsevier Ltd., 2015)
Family Caregiving in the New Normal discusses how the drastic economic changes that have occurred over the past few years have precipitated a new conversation on how family care for older adults will evolve in the future. This text summarizes the challenges and potential solutions scientists, policy makers, and clinical providers must address as they grapple with these changes, with a primary focus given to the elements that may impact how family caregiving is organized and addressed in subsequent decades, including sociodemographic trends like divorce, increased participation of women in the workforce, geographic mobility, fewer children in post-baby boom families, chronic illness trends, economic stressors, and the current policy environment. A section on the support of caregivers includes technology-based solutions that examine existing models, personal health records, and mobile applications, big data issues, decision-making support, person-centered approaches, crowd-sourced caregiving such as blogs and personal websites that have galvanized caregivers, and new methods to combine paid and unpaid forms of care.
Conclusion -- 18.A Perfect Storm? The Future of Family Caregiving / Robert L. Kane.
Vendor-supplied metadata.
Includes bibliographical references and index.
Keywords: Caregivers -- United States; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; Caregivers; United States; Caregivers; Family Relations; Socioeconomic Factors; Electronic books; Electronic book